2015
DOI: 10.1080/15228835.2014.998573
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Child Welfare Workers’ Opinions of Using Video Assisted Visitation (VAV) in the Family Reunification Process

Abstract: Based on a survey of 40 social workers using video assisted visitation as part of family reunification work, this study identifies its perceived advantages and disadvantages. The advantages included connecting to the team, relationship maintenance, therapeutic value, access due to distance, and the added visual component. The disadvantages included the technology, age of the child, limitations of not being in person, and fear VAV would replace in-person visits. The discussion describes how to capitalize on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Two studies reported on the perspective of both birth parents and children (Wolman & Pomerance, 2012;Yarosh et al, 2009). The remaining studies explored only the perspective of professionals (Quinn, 2015;Saini & Polak, 2018) or parents (Castelain-Meunier & Libbrecht, 1997;Dworkin, 2016;Maupas, 2019). Finally, four studies combined qualitative and quantitative methods, one study used a quantitative design, and six used a qualitative design.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Two studies reported on the perspective of both birth parents and children (Wolman & Pomerance, 2012;Yarosh et al, 2009). The remaining studies explored only the perspective of professionals (Quinn, 2015;Saini & Polak, 2018) or parents (Castelain-Meunier & Libbrecht, 1997;Dworkin, 2016;Maupas, 2019). Finally, four studies combined qualitative and quantitative methods, one study used a quantitative design, and six used a qualitative design.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Separation from parents can be extremely stressful for children, increasing their risk for adjustment difficulties (Kobak et al, 2016). In order to bridge the gap created by separation between children and their loved ones, virtual contact has been utilized in a number of areas of family life including families with incarcerated parents (McLeod & Bonsu, 2018;Phillips, 2012;Skora & Poehlmann-Tynan, 2020), military families (Mathew-Juarez et al, 2013;Mogil et al, 2015), families with divorced parents (LaMarca, 2012;Saini & Polak, 2018;Saini et al, 2013), extended family members (e.g., grandparents) (McClure et al, 2018) and child welfare families (Iyer et al, 2020;Neil et al, 2020;Quinn et al, 2015). Research in these areas has found that children can benefit significantly in terms of knowledge development, emotional well-being and relationship maintenance from virtual communication with parents and others from whom they are separated.…”
Section: Virtual Parent-child Communicationmentioning
confidence: 99%
“…There is little research on the use of virtual visitation to satisfy statutory requirements for parentchild contact during juvenile dependency proceedings, or on the effectiveness of such contact on foster children's well-being and their relationship with birth family members (Birnbaum, 2020). Existing research and literature reviews point to a number of perceived advantages and disadvantages in using smartphones and video assisted visitation, as well as challenges in implementing such visitation, in child welfare cases (Iyer et al, 2020;Neil et al, 2020;Quinn et al 2015). In the sections to follow we highlight the findings of Neil et al (2020), the only study, to date, providing empirical data on the experiences and perspectives of key stakeholders related to virtual contact between foster youth and their birth families during the pandemic lockdown; this is followed by a more general review of the benefits and drawbacks of virtual parent-child communication in support of family reunification in juvenile dependency cases.…”
Section: Implementing Virtual Parent-child Visitation In Juvenile Depmentioning
confidence: 99%
“…Software programs have been developed in child welfare to facilitate communication and information exchange between case managers and care providers (Dodsworth et al, 2013). Real-time video technologies such as Skype and Facetime have been used to support visitation between children and parents (Quinn, Sage, & Tunseth, 2015). The use of the internet in various aspects of service delivery can extend the availability of services and help clients avoid the stigma associated with going to an agency (Ramsey & Montgomery, 2014).…”
Section: Literature Review Social Media Use In Human Servicesmentioning
confidence: 99%